2009
DOI: 10.1093/hmg/ddp193
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of three independent SNPs greatly increase the risk estimate for RA at 6q23

Abstract: The most consistent finding derived from the WTCCC GWAS for rheumatoid arthritis (RA) was association to a SNP at 6q23. We performed a fine-mapping of the region in order to search the 6q23 region for additional disease variants. 3962 RA patients and 3531 healthy controls were included in the study. We found 18 SNPs associated with RA. The SNP showing the strongest association was rs6920220 [P = 2.6 × 10−6, OR (95% CI) 1.22 (1.13–1.33)]. The next most strongly associated SNP was rs13207033 [P = 0.0001, OR (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 18 publications
3
40
0
3
Order By: Relevance
“…Given its key function in the fine-tuning of NF-jB signalling, it should be expected that defects in TNFAIP3 expression or function could lead to chronic inflammation and tissue damage. Recent findings have revealed a crucial link between polymorphisms in the human TNFAIP3 locus and a wide spectrum of human autoimmune and inflammatory diseases (Eldor et al 2006;Nenci et al 2007;Graham et al 2008;Musone et al 2008;Orozco et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Given its key function in the fine-tuning of NF-jB signalling, it should be expected that defects in TNFAIP3 expression or function could lead to chronic inflammation and tissue damage. Recent findings have revealed a crucial link between polymorphisms in the human TNFAIP3 locus and a wide spectrum of human autoimmune and inflammatory diseases (Eldor et al 2006;Nenci et al 2007;Graham et al 2008;Musone et al 2008;Orozco et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the expression level of A20 in RA-FLSs was lower than that in OA-FLSs (Elsby et al, 2010). Although the difference was not significant, this finding could provide in vitro evidence of altered A20 transcription by 6q23 intergenic SNPs associated with RA (Dieguez-Gonzalez et al, 2009;Orozco et al, 2009). Thus, we speculated that the down-regulation of NF-B inhibitors might be a possible mechanism for enhanced activation of NF-B in high-responder FLSs.…”
Section: Possible Positive Effect Of A20/abins On Pro-inflammatory Cymentioning
confidence: 75%
“…Как и в подавляющем боль-шинстве исследований, ассоциативная взаимосвязь с по-лиморфизмами имеет разнонаправленный вектор: ми-норные аллели полиморфизмов rs675520 и rs6920220 -положительно, а rs10499194 -отрицательно ассоциирова-ны с РА. Необходимо отметить, что в GWAS и других крупномасштабных исследованиях пик ассоциативной связи приходится на межгенный регион хромосомы 6q23, между генами OLIG3 и TNFAIP3 (известен также как А20) [33][34][35][36][37]. Данный участок хромосомы не содержит после-довательностей, кодирующих какие-либо известные к на-стоящему времени белки.…”
Section: Mcp1/ccl2 Icam1unclassified